2005
DOI: 10.1242/jeb.01689
|View full text |Cite
|
Sign up to set email alerts
|

A concept of dietary dipeptides: a step to resolve the problem of amino acid availability in the early life of vertebrates

Abstract: SUMMARY The premise that a dietary dipeptide approach will improve the understanding of amino acid utilization in the fastest-growing vertebrate, the teleost fish, was tested by examining the muscle free amino acid (FAA) pool and enzyme activities, in concert with growth response, when dietary amino acids were provided in free, dipeptide or protein molecular forms. We present the first evidence in fish that, in response to a synthetic dipeptide diet,muscle FAA varies as a result of both growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 43 publications
2
29
0
2
Order By: Relevance
“…In contrast, juvenile rainbow trout Oncorhynchus mykiss growth experiment (Terjesen et al 2006) showed that amino acid in dipeptide form was efficiently absorbed than an identical amino acid in free form that resulted in higher accumulation rate and postprandial peak time for muscular free amino acid. This may indicate different metabolic handling of amino acids and availability for protein synthesis, which is translated to better growth rate (Dabrowski et al 2005). Juvenile fish study indicated a faster free amino acid absorption compared with protein bound amino acids for carp, Cyprinus carpio (Plakas and Katayama 1981), rainbow trout (Cowey and Walton 1988) and Atlantic cod, Gadus morhua (Berge et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, juvenile rainbow trout Oncorhynchus mykiss growth experiment (Terjesen et al 2006) showed that amino acid in dipeptide form was efficiently absorbed than an identical amino acid in free form that resulted in higher accumulation rate and postprandial peak time for muscular free amino acid. This may indicate different metabolic handling of amino acids and availability for protein synthesis, which is translated to better growth rate (Dabrowski et al 2005). Juvenile fish study indicated a faster free amino acid absorption compared with protein bound amino acids for carp, Cyprinus carpio (Plakas and Katayama 1981), rainbow trout (Cowey and Walton 1988) and Atlantic cod, Gadus morhua (Berge et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if the number of transporters is limited, the uptake profile will have a longer duration. By contrast, AAs absorbed via passive carriers and diffusion will be concentration dependent, and small peptides are known to be absorbed more rapidly (Steinhardt and Adibi, 1986;Matthews, 2000;Bogé et al, 2002;Dabrowski et al, 2005). …”
Section: Free Amino Acid Uptake Profilesmentioning
confidence: 99%
“…PepT1 is one of key intestinal transporters, which play an important role in regulating oligopeptide transportation (Daniel 2004;Terova, Robaina, Izquierdo, Cattaneo, Molinari, Bernardini & Saroglia 2013). Accumulating evidence demonstrates that PepT1 and diverse AA transporters may have a major role in regulating body AA homoeostasis (Dabrowski, Terjesen, Zhang, Phang & Lee 2005;Bakke, Jordal, G omez-Requeni, Verri, Kousoulaki, Aksnes & Rønnestad 2010;Xu, He, Mai, Zhou, Xu & Song 2016b). Large amounts of peptides and amino acids were transported by the PepT1 and AA transporters across cell membrane, providing essential nutrients for growth and metabolism (Poncet & Taylor 2013).…”
Section: Introductionmentioning
confidence: 99%